BRECCIA DIKES AND CRATER-RELATED FAULTS IN IMPACT CRATERS ON MARS: EROSION AND EXPOSURE ON THE FLOOR OF A CRATER 75 KM IN DIAMETER AT THE DICHOTOMY BOUNDARY - Head J.W.; Mustard J.F. (My University, 2006)
Environmental conditions on Mars are conducive to the modification and erosion of impact craters, potentially revealing the nature of their substructure. On Earth, postimpact erosion of complex craters in a wide range of target rocks has revealed the nature and distribution of crater-related fault structures and a complex array of breccia and pseudotachylyte dikes, which range up to tens of meters in width and tens of kilometers in length. We review the characteristics of fault structures, breccia dikes, and pseudotachylyte dikes on Earth, showing that they occur in complex network-like patterns and are often offset along late-stage crater-related faults. Individual faults and dikes can undulate in width and can branch and bifurcate along strike. Detailed geological analyses of terrestrial craters show that faults and breccia dikes form during each of the major stages of the impact-cratering process (compression, excavation, and modification). We report here on the discovery of prominent, lattice-like ridge networks occurring on the floor of a highly modified impact crater 75 km in diameter near the dichotomy boundary of the northern lowland and southern upland. Interior fill and crater-floor units have been exhumed by fluvial and eolian processes to reveal a unit below the crater floor containing a distinctive set of linear ridges of broadly similar width and forming a lattice-like pattern. Ridge exposures range from ~1-4 kin in length and ~65-120 in in width, are broadly parallel, straight to slightly curving, and are cross-cut by near-orthogonal ridges, forming a box or lattice-like pattern. Ridges are exposed on the exhumed crater floor, extending from the base of the wall toward the center. On the basis of the strong similarities of these features to terrestrial crater-related fault structures and breccia dikes, we interpret these ridges to be faults and breccia dikes formed below the floor of the crater during the excavation and modification stages of the impact event, and subsequently exhumed by erosion. The recognition of such features on Mars will help in documenting the nature of impact-cratering processes and aid in assessment of crustal structure. Faults and breccia dikes can also be used as data for the assessment of post-cratering depths and degrees of landform exhumation. © The Meteoritical Society, 2006.